Identifying the Executive Factors of Social Audit in Attracting Deposits and Reducing the Cost of Money in Bank using Grounded Theory Method - Felehgari, Mokhtar; Jamshidinavid, Babak; Ghanbari, Mehrdad; Mohammadi Yarijani, Forouzan (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2023)
Objective: The purpose of this research is to identify practical indicators for the practical implementation of social audit in attracting deposits and reducing the cost of money in banks using the theoretical method.Method: In this research, using the qualitative research method of Strauss and Corbin (2011) grounded theory with the Nizamand method, the social audit model has been developed in attracting deposits and reducing the cost of money in banks. Therefore, in order to collect information from the statistical population used, which includes banking and university experts who have doctorate degrees in accounting, management, or economics, a semi-structured interview was conducted with 21 of them using purposive sampling, and the analysis of information in three The stage of open coding, axial coding and selective coding has been done.Findings: According to the results of the data analysis of the interviews in three stages of open, central and selective coding, the category "social audit in attracting deposits and reducing the cost of money in the bank" was chosen as the central category, and this type of audit through evaluation and examining compliance with social responsibilities in terms of attracting low-cost deposits, reducing bank non-current claims, developing virtual banking services, respecting depositors' rights, respecting government rights, protecting the environment, reducing organizational administrative costs, and respecting competitors' rights is doneThe causal conditions of the model include the need of the group of shareholders, the government, depositors and environmentalists for social intelligence information in attracting deposits and reducing the cost of money in banks, and the strategies for conducting this audit also include optimizing corporate governance in banks, creating anti-corruption committees, Fraud and money laundering, government incentive policies, continuous training of employees, respecting the interests of all stakeholders and giving importance to high cultural and social values in the workplace. Also, factors such as the lack of attention to transparency and greater profitability in state banks, government laws, the complexity of the nature of social audit implementation, and the lack of accounting and social audit standards were the most important intervening factors that affect the model's strategies.Conclusion: In the country of Iran, if the executive factors of social audit in attracting deposits and reducing the cost of money, which have been identified during the development of the model in this research, will be implemented by the banks. It can be ensured that the banks fulfilled their social responsibilities in the field of attracting deposits, which prevented their bankruptcy in the first stage and prevented social financial crises in the society in the second stage.